Comparative Analysis of the Mechanical Properties of Polymer Matrix Composites Reinforced with Fiberglass Fabric - Daniela Spasova (UIKTEN, 2021)
The composites materials are increasingly displacing the traditional ones and are the most widely used of all groups of engineering materials. Polymer matrix composites have the greatest application and they are used for equipment operating in the sea-water environment and polymer pipes. In this article, the mechanical properties of six types of polymer matrix composites reinforced with fiberglass fabric are considered and analyzed. Two types of resin were used for the matrix – polyester resin and vinyl ester resin. The both types of matrices are reinforced with three different fiberglass fabric- monoaxial, biaxial and triaxial fiberglass. The investigated composites are obtained by mechanical pressing in the form of sixlayer panels. A comparative analysis of tensile strength and banding strength of the six types investigated composites was made. A macrofractographic analysis of the structure was also performed.